Salmonella-induced changes of the rat intestinal microbiota - Bukina, Yu. V.; Polishchuk, N. N.; Bachurin., H. V.; Cherkovskaya, O.S.; Zinych, O.L.; Lazaryk., O.L.; Bezugly, M.B.; Поліщук, Наталія Миколаївна; Бачурін, Георгій Вікторович; Черковська, Ольга Степанівна; Зінич, Олена Леонідівна; Лазарик, Олександра Леонідівна; et al. (My University, 2021)
The gut microbiome profoundly affects the body functioning: it participates in host protection against pathogenic microorganisms, metabolic events, inhibition of inflammatory responses, formation of innate and adaptive immune response in the intestinal mucosa. One of the causes altering microbiota community is due to antibiotics. Therefore, the processes of antibiotics interaction together with Salmonella enteritidis and Salmonella typhimurium with representatives of normal intestinal microflora are of particular interest. Materials and methods. The quantitative and qualitative analysis of the wall microbiota composition in rats was evaluated by bacteriological method, the statistical data analysis was performed using the software StatSoft Statistica v.12. Results and discussion. Inoculation of vancomycin and S. enteritidis, S. typhimurium in groups II, III, IV resulted in quantitatively decreased E. coli level by 10-, 7- and 110-fold, respectively (p ≤ 0.05). The count of P. aeruginosa decreased markedly only in the group III (p ≤ 0.05). The count of Bacteroides spp. members was profoundly decreased by several thousand times (group II) as well as 70- and 87-fold (groups III and IV), respectively (p ≤ 0.05). The count of E. faecalis and E. faecium decreased by 861-, 6- and several thousand times (groups II, III, IV), respectively (p ≤ 0.05). The count of Proteus spp. markedly decreased in group II by 27-fold and rapidly increased in group IV (p ≤ 0.05). Group III revealed a sharp decline in level of Enterobacter spp. and Klebsiella spp. by 847- and 150-fold, whereas in group II they were increased by 7- and 46-fold, respectively (p ≤ 0.05). The count of Staphylococcus spp. decreased by 10-fold only in group II. The level of Clostridium spp. decreased by several thousand times (group II) and by 5,500 times (group IV) (p ≤ 0.05). The count of Lactobacillus spp. decreased by several thousand times (group II). The count of Bifidobacterium spp. members significantly decreased by 10.9-fold and by several thousand times (groups III, IV). The level of Peptostreptococcus anaerobius profoundly decreased in all three study groups (p ≤ 0.05). The level of Salmonella spp. increased in group II by 49 times, but markedly increased in groups III and IV (p ≤ 0.05). Inoculation of Salmonella after vancomycin pretreatment caused dramatic change in the microbiota composition in groups V and VI, namely: increased count of E. coli by 65- and 105-fold, markedly increased level of P. aeruginosa in group V and VI — by 3-fold. In addition, these groups also showed decreased level of Bacteroides spp. by 9- and 10-fold (p ≤ 0.05). The count of E. faecalis and E. faecium decreased dramatically only in group V (p ≤ 0.05). The count of Proteus spp. decreased by 17 times in group V as well as in group VI (p ≤ 0.05). A sharp increase in level of Enterobacter spp. and Klebsiella spp. members was observed in groups V and VI (p ≤ 0.05). However, representatives of Peptostreptococcus anaerobius in groups V and VI decreased by 20 and 9 times, respectively (p ≤ 0.05). The count of Salmonella spp. decreased only in group V by 7 times (p ≤ 0,05). Inoculating experimental animals with B. fragilis conditioned with S. enteritidis, S. typhimurium and pretreated with vancomycin resulted in markedly decreased level of E. coli in group VII and VIII by 538 times (p ≤ 0.05). The count of P. aeruginosa in groups VII and VIII decreased profoundly, whereas level of Bacteroides spp. members was reciprocally increased (p ≤ 0.05). The level of Lactobacillus spp. decreased by 10.3 times only in group VI. The count of E. faecalis and E. faecium increased by 10 and 19 times in groups VII and VIII, respectively, whereas level of Proteus spp. decreased only in group VII by 322 times (p ≤ 0.05). In addition, a sharp decrease in level of Enterobacter spp. and Klebsiella spp. members (p ≤ 0.05) was found in groups VII and VIII. The count of Peptostreptococcus anaerobius and Lactobacillus spp. members was markedly increased by 7-, 12-, several thousand-fold and 40 times (groups VII and VIII, respectively) (p ≤ 0.05). The count of S. enteritidis and S. typhimurium in groups VII and VIII decreased rapidly (p ≤ 0.05). Conclusion. Inoculation of B. fragilis can be used in treatment of inflammatory bowel diseases or disorders with impaired gut barrier function. Микробиом кишечника существенно влияет на функционирование организма: он участвует в защите организма от патогенных микроорганизмов, в процессах обмена веществ, торможении воспалительных реакций, в формировании врожденного и адаптивного иммунного ответа в слизистой оболочке кишечника. Одной из причин изменения микробиоты является использование антибиотиков. Поэтому процессы взаимодействия антибиотиков, Salmonella enteritidis и Salmonella typhimurium, с представителями нормальной микрофлоры кишечника представляют особый интерес. Материалы и методы. Проведен количественный и качественный анализ состава микробиоты стенки у крыс бактериологическим методом, а также статистический анализ данных с использованием программы StatSoft Statistica v.12. Результаты и обсуждение. При введении ванкомицина и S. enteritidis, S. typhimurium в группы II, III, IV наблюдалось снижение количественного содержания кишечной палочки в 10, 7 и 110 раз соответственно (р ≤ 0,05). Количество P. aeruginosa значительно уменьшилось только в третьей группе (р ≤ 0,05). Количество представителей Bacteroides spp. значительно уменьшилось в несколько тысяч раз (группа II) и в 70 и 87 раз (группы III и IV) (р ≤ 0,05). Содержание E. faecalis и E. faecium уменьшилось в 861, 6 и в несколько тысяч раз (группы II, III, IV) (р ≤ 0,05). Количество Proteus spp. значительно уменьшился во II группе в 27 раз и быстро увеличился в IV группе (р ≤ 0,05). Группа III показала резкое снижение содержания представителей Enterobacter spp. и Klebsiella spp. в 847 и 150 раз, а во II группе наблюдается увеличение их числа в 7 и 46 раз соответственно (р ≤ 0,05). Количество Staphylococcus spp. снизилось в 10 раз только во II группе. Количественное содержание Clostridium spp. снизилось в несколько тысяч раз (группа II) и в 5,5 раз (группа IV) (р ≤ 0,05). Количество Lactobacillus spp. уменьшилось в несколько тысяч раз (группа II). Количество представителей Bifidobacterium spp. значительно снизилось в 10,9 раз и в несколько тысяч раз (группы III, IV). Количественное содержание Peptostreptococcus anaerobius значительно уменьшилось во всех трех группах исследования (p ≤ 0,05). Содержание Salmonella spp. увеличилось во II группе в 49 раз, а значительное увеличение наблюдалось в III и IV группах (р ≤ 0,05). Введение сальмонеллы на фоне предварительной обработки ванкомицином вызывает резкое изменение состава микробиоты в группах V и VI, а именно увеличение количества кишечной палочки в 65 и 105 раз, значительное увеличение содержание P. aeruginosa в V группе, а в VI — в 3 раза. Также в этих группах наблюдается уменьшение количества Bacteroides spp. 9 и 10 раз (р ≤ 0,05). Содержание E. faecalis и E. faecium значительно снизилось только в пятой группе (р ≤ 0,05). Количество Proteus spp. уменьшается в 17 раз в группе V, а также значительно снижается в группе VI (р ≤ 0,05). Резкое увеличение количества представителей Enterobacter spp. и Klebsiella spp. наблюдалось в группах V и VI (р ≤ 0,05). Однако представителей Peptostreptococcus anaerobius в V и VI группах стало меньше в 20 и 9 раз соответственно (р ≤ 0,05). Количество Salmonella spp. снизилось только в V группе в 7 раз (р ≤ 0,05). При введении подопытным животным B. fragilis, получавшим S. enteri tidis и S. typhimurium на фоне предварительной обработки ванкомицином, отмечалось значительное снижение уровня кишечной палочки в группе VII, а в VIII — в 538 раз (р ≤ 0,05). Количество P. aeruginosa в группах VII и VIII значительно уменьшилось, а число представителей Bacteroides spp. естественно увеличивается (р ≤ 0,05). Содержание Lactobacillus spp. снизилось в 10,3 раза только в VI группе. Содержание E. faecalis и E. faecium увеличилось в 10 и 19 раз в VII и VIII группах соответственно, а количество Proteus spp. уменьшилось только в VII группе в 322 раза (р ≤ 0,05). Также в VII и VIII группах наблюдалось резкое снижение количества представителей Enterobacter spp. и Klebsiella spp. (р ≤ 0,05). Число представителей Peptostreptococcus anaerobius и Lactobacillus spp. значительно увеличилось в 7, 12 раз и в несколько тысяч и 40 раз (группы VII и VIII соответственно) (р ≤ 0,05). Количество S. enteritidis и S. typhimurium в VII и VIII группах интенсивно снижалось (р ≤ 0,05). Выводы. Введение B. fragilis может быть использовано при лечении воспалительных заболеваний кишечника или заболеваний с нарушением барьерной функции кишечника.
Сальмонелла-индуцированные изменения кишечного микробиома крыс
Keywords: parietal microbiota; microbiome; vancomycin; Salmonella; bacteroid; rats; пристеночная микробиота; микробиом; ванкомицин; сальмонелла; бактероиды; крысы